INDONESIAN CONSUMER PREFERENCES IN SELECTING MASSIVE OPEN ONLINE COURSES (MOOCS): A CONJOINT ANALYSIS STUDY - Putri, Nanda Alifia; Hidayati, Aprihatiningrum (Universitas Pakuan, 2025)
ABSTRACTThis paper attempts to measure and analyze consumer preferences when deciding to use massive open online courses (MOOCs). The research examines the challenges faced by Indonesian EdTech companies, particularly MOOCs, in offering diverse training sessions without considering the quality, substance, and efficiency of students' learning. This study employs descriptive quantitative research with a conjoint analysis approach to examine five key attributes: learning methods, teaching staff, prices, educational topics, and supporting services. The population is all Indonesian people aged 15–34, who are the target market of online course service providers. A total of 436 respondents were gathered by distributing online surveys. This study presents findings about the utility value and importance of the factors that influence consumer preferences. These findings reveal that price and topic are the primary factors influencing consumer preferences for online courses. It also shows the kinds of combinations of services and features that customers perceive to be important. This study contributes to the field of marketing, especially consumer preferences.ABSTRAKPenelitian ini bertujuan untuk mengukur dan menganalisis preferensi konsumen dalam menggunakan massive open online courses (MOOCs). Penelitian ini mengkaji tantangan yang dihadapi oleh perusahaan EdTech Indonesia, khususnya MOOCs, dalam menawarkan berbagai sesi pelatihan tanpa mempertimbangkan kualitas, substansi, dan efisiensi pembelajaran siswa. Studi ini menggunakan penelitian deskriptif kuantitatif dengan pendekatan analisis conjoint untuk meneliti lima atribut utama: metode pembelajaran, pengajar, harga, topik pendidikan, dan layanan pendukung. Populasi penelitian adalah masyarakat Indonesia berusia 15–34 tahun, yang merupakan target pasar penyedia layanan kursus online. Sebanyak 436 responden dikumpulkan melalui survei online. Hasil penelitian menunjukkan nilai utilitas dan pentingnya faktor-faktor yang memengaruhi preferensi konsumen. Temuan ini mengungkapkan bahwa harga dan topik merupakan faktor utama yang memengaruhi preferensi konsumen dalam memilih kursus online. Selain itu, penelitian ini menunjukkan kombinasi layanan dan fitur yang dianggap penting oleh pelanggan. Penelitian ini berkontribusi pada bidang pemasaran, khususnya preferensi konsumen.